Design of dual-band b-shaped monopole antenna for MIMO application - Iddi, Hashim Uledi (2012)
A dual-band B-shaped monopole antenna for MIMO application is presented. The proposed antenna consists of B-shaped element which operates at dual band frequencies of 2.45GHz and 5.8GHz. The prototype has been fabricated and when tested, the impedance bandwidths are 29.9% and 33.8% for 2.45GHz and 5.8GHz, respectively. Good agreement between the measurement and simulation results in term of return loss and radiation pattern have been obtained.